Mielekäs tutkimus näkökulmia sosiaalityön tutkimuksen missioihin - Enroos, Rosi; Ranta-Tyrkkö, Satu; Mäntysaari, Mikko (Tampere University Press, 2017)
"Meaningful Research. Perspectives on the Missions of Social Work is a collection of articles discussing the meanings, missions and meaningfulness of social work research. The open access book celebrates the anniversary of Tarja Pösö and her career as distinguished Professor of Social Work in the University of Tampere. Edited by Rosi Enroos, Mikko Mäntysaari and Satu Ranta-Tyrkkö, the book asks what kind of elements make social work research meaningful and does social work research have a particular mission and specific ethical and moral obligations, when compared to other disciplines. The research on social work research being scanty in Finland, the book expands the discussion on the particular nature of social work research. Meaningful Research discusses social work research in general and the research of child protection in particular. The book consists of an introductory chapter and two thematic sections, Vantage Points to the Meaningfulness and Missions, and Meaningfulness and Missions of Child Protection Research. The former section covers wide range of issues from concerns regarding the training of new social work researchers, change and time as the methodologically central elements of social work, the meaningfulness of social work practice, and the future ethics of social work in a world of globally evolving risks. The second, child protection specific section analyses demanding situations in substitute care, the methodologically meaningful research concerning the function of youth residential care, the legitimacy and resources of child protection research in Finland, ending with an English language article that elaborates on the meaningfulness of comparative research on child protection systems. The book is directed to social work researchers and practitioners, as well as to teachers and students of social work and social welfare, and anyone interested in research based development of social work. "